State of the art measurements with TexAT. (August 2019) - Bishop, J; Rogachev, G V; Aboud, E; Ahn, S; Assunção, M; Barbui, M; Bosh, A; Guimarães, V; Hooker, J; Hunt, C; Jayatissa, D; Koshchiy, E; et al.
Abstract: In the past several years, there has been a large interest of Time Projection Chambers (TPCs) for use in experimental nuclear physics. This has continued in tandem with the requirement for high efficiency detectors with low intensity radioactive ion beams. TexAT is a Active Target TPC (AT-TPC) built at Texas A&M University utilizing MICRO MEsh GASeous (MicroMegas) pads and GET electronics developed specifically for TPCs. This design combines good TPC pixelation with a surrounding shell of Si/CsI telescopes to make an extremely versatile detector capable of a wide range of different experimental techniques with only minor modifications to the electronics setup. Two recent experiments performed at the Cyclotron Institute, Texas A&M University, are detailed here demonstrating versatility beyond the usual Thick Target Inverse Kinematics (TTIK) or transfer reactions that these TPCs are more typically used for. The first, a measurement of the 12 N → 12 C * → 3α decay demonstrates the capabilities of TexAT as a low-energy detector operating at low pressure (20 Torr) to measure β-delayed particle decay. The second, a direct measurement of the 8 B+ 40 Ar fusion cross section shows the advantages of operating in active target mode where the target also functions as the detector gas.